Improving Arabic Vocabulary Mastery Through Interactive Wordwall Game Media - Devy Habibi Muhammad; Alda Eky Nur K; Lailtul Izzah; Nadiah Yusfi Nabilah (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to improve the mastery of Arabic vocabulary through the use of the interactive game media WordWall at SMP Muhammadiyah 3 Gending, Probolinggo Regency. The research method used is Participatory Action Research (PAR) with 17 eighth-grade students as the research subjects. This research was conducted in two stages, namely the pre-cycle and cycle 1, with measurements of learning outcomes before and after the use of WordWall. The research results show that before the use of WordWall media, the percentage of students achieving mastery was 82%, while after implementation it increased to 100%. This improvement reflects the effectiveness of using WordWall in facilitating students' understanding and memorization of vocabulary, while also enhancing their motivation and engagement in learning. In conclusion, the use of WordWall media has proven to be an innovative and effective method in improving Arabic vocabulary mastery. The implementation of technology in language learning can help students achieve better learning outcomes, as well as create a more engaging and interactive learning experience.